1986
DOI: 10.1113/jphysiol.1986.sp016193
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between long‐term potentiation and release of endogenous amino acids from dentate gyrus of anaesthetized rats.

Abstract: SUMMARY1. The relationship between long-term potentiation (l.t.p.) and the release of endogenous amino acid transmitters has been investigated in the dentate gyrus of rats anaesthetized with urethane.2. The molecular layer was perfused with artificial cerebrospinal fluid using a push-pull cannula. The perfusate was collected and analysed for glutamate, aspartate, glycine, glutamine and y-aminobutyric acid (GABA) using high-performance liquid chromatography (h.p.l.c.) with fluorometric detection.3. Recording el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
65
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(72 citation statements)
references
References 44 publications
(51 reference statements)
6
65
0
Order By: Relevance
“…Furthermore the experiments of Bliss and co-workers indicate that LTP is maintained, at least in part, by a sustained increase in transmitter (e.g. glutamate) release (Bliss et al, 1988(Bliss et al, , 1986Errington et al, 1987;Lynch et al, 1989a). These findings were challenged by Ben-Ari and co-workers (Anikszteijn et al, 1989(Anikszteijn et al, , 1991, but confirmed by recent observations in our group (Ghijsen and Lopes da Ghijsen et al, 1992).…”
Section: Introductionsupporting
confidence: 74%
“…Furthermore the experiments of Bliss and co-workers indicate that LTP is maintained, at least in part, by a sustained increase in transmitter (e.g. glutamate) release (Bliss et al, 1988(Bliss et al, , 1986Errington et al, 1987;Lynch et al, 1989a). These findings were challenged by Ben-Ari and co-workers (Anikszteijn et al, 1989(Anikszteijn et al, , 1991, but confirmed by recent observations in our group (Ghijsen and Lopes da Ghijsen et al, 1992).…”
Section: Introductionsupporting
confidence: 74%
“…Thus, there is evidence to support modifications presynaptically (Bliss et al, 1986;Malgaroli and Tsien, 1992;Bolshakov and Seigelbaum, 1994;Stevens and Wang, 1994), postsynaptically (Davies et al, 1989;Zalutsky and Nicoll, 1990;Manabe et al, 1992;Isaac et al, 1995;Liao et al, 1995;Oliet et al, 1996), and even on different postsynaptic receptors (Muller and Lynch, 1988;Kullman, 1994;Selig et al, 1995). Our experiments suggest that these modifications are maintained by autonomous PKC phosphorylation that is increased or decreased by the pattern of ongoing afferent activity.…”
Section: Pkm and The Divergence And Convergence Of Signal Transductiomentioning
confidence: 53%
“…The mechanism could involve presynaptic changes (increased glutamate release), postsynaptic changes (increased number of AMPA receptors or changes of the binding properties of AMPA receptors), or glial changes (reduced uptake of glutamate by glial cells) [Bindman et al, 19911. Indeed, the issue is complex because there is evidence in favor of all these changes, some of it contradictory [Bliss et al, 1986;Foster and McNaughton, 1991;Tsumoto, 1992;Voronin, 19891. At this time, perhaps the most favored hypothesis is that LTP is maintained through a combination of pre-and postsynaptic mechanisms, a combination which may be different in different synapses and that might, in some, include morphological or extrasynaptic changes [Bindman et al, 1991;Bliss and Collingridge, 1993;Colley and Routtenberg, 1993;Hawkins et al, 19931. There is now little doubt that protein phosphorylation, perhaps of glutamatergic receptors, and perhaps mainly through the intervention of PKC, is crucial for the first 3 or so hours of the maintenance phase [Colley and Routtenberg, 1993;Reymann et al, 19881, and that later other mechanisms enter into play, like protein synthesis and gene expression [see Colley and Routtenberg, 1993;Sheu et al, 19931. After 3 h, LTP can be blocked by protein synthesis inhibitors, the best studied of which is anisomycin applied to CA1 slices [Frey et al, 19881 or to the dentate gyrus in freely moving rats [Matthies, 19891.…”
Section: Ltp Maintenancementioning
confidence: 99%